Implikatur dan Prinsip Kesantunan dalam Podcast (PWK) Praz Teguh Bersama Gazellecross: Kajian Pragmatik - Nur Kholida Hanum; Misbahul Khanif; Taswirul Afkar (Journal Innovation In Education, 2025)
This research examines the implicature and politeness principles in Praz Teguh's Warung Kopi (PWK) Podcast with Grazellecross. Through a pragmatic approach, the research reveals how conventional and conversational implicatures are applied and how politeness maxims maintain social relations. Grice's implicature theory and Leech's politeness maxims are used to analyze the speech in the podcast. The results of the analysis conducted show that in the podcast there are conventional and conversational implicatures. Politeness principles, such as the maxim of wisdom, the maxim of generosity, the maxim of respect, the maxim of simplicity, the maxim of agreement, and the maxim of sympathy are also found in the conversations in the podcast and become the key in creating a harmonious atmosphere of interaction. This research aims to know conceptually and analytically how implicature and politeness principles work in a communication. In addition, to analyze how speakers convey their intentions indirectly, as well as how they apply civility strategies in maintaining social relations.